The harmful Effects of Monosodium Glutamate on Blood Parameters Liver and Kidney Functions In Adult White Rats and the Protective Role of Omega-3 - Thoalffakar A. ALhamed; Farah A. Al-marzook; Abdulridha Mohammed Al-Asady (Institute of Medico-legal Publications Pvt Ltd, 2021)
The present study was conducted to find out the harmful effect of exposure to monosodium glutamate(MSG) on laboratory animal weight, hematological and biochemical parameters on rats of 10 -15 weeksold and weight of 100-200 g. Whereas, this study was conducted in the Basic Sciences Branch - College ofNursing - University of Warith Alanbiyaa From 11/1/2019 to 2/1/2020, the animals were divided into fourgroupsG 1- Control The first group controlG 2- MSG (1.8mg / kg) Group IIG 3 - MSG (1.8 mg / kg) + omega-3 (0.8 mg / kg) Group IIIG 4 - MSG (1.8 mg / kg) + omega-3 (1.2 mg / kg) Group IVWhere the four groups were fed according toThe above distribution is according to the concentrations in each group effect of MSG at one oral low doseof 1.8 mg/g body wt. on liver and kidney functions in albino rats. The possible protective effect of omega3 (at oral dose of 0.8 mg/g body wt.) (at oral dose of 1.2 mg/g body wt.) against MSG induced hepatic andrenal stress was also investigated of mono-sodium glutamate for 30 days.The results showed a significant decrease (p <0.05) in blood parameters, including RBC count 5.1 ±0.7 andconcentration of PCV: 14.5 ±0.33, MCH: 34.5 ± 2.77, MCV: 96.5 ±3.21, MCHC: 34.0 ± 0.89. Comparedwith the control group indicating anemia in MSG treated animals.There was a significant increase in the biochemical parameters (AST: 216 ± 14.8, ALT 3.6 ± 0.40, ALP144.75± 6.55). And also in the Urea - Creatinine kidney standardsWhich represents the liver function in animals treated with monosodium glutamate compared with thecontrol group, despite a significant increase (P <0.05) in the level of urea 2.70 ± 0.07 and creatinine 0.098 ±0.005 in the blood in the animal treated with MSG compared with the control group.